PENCEGAHAN TINDAK PIDANA PENCURIAN DENGAN PEMBERATAN MELALUI PERAN PATROLI RODA DUA SATUAN SABHARA DI WILAYAH HUKUM POLRES BOGOR - HARIANTO, FAUZAN MAULANA (Advances in Police Science Research Journal, 2019)
Indonesia is the fourth largest country that has the most population in the world. This certainly has a view on the negative side and also the positive side. This research was carried out at Polres Bogor, interviewing the police, especially the Sabhara section. And the authors also conducted a qualitative analyzed study then presented descriptively, namely by parsing, explaining and describing in accordance with the problems closely related to this study. The use of qualitative analysis techniques covers all the data that has been obtained, thus forming a description that supports the qualifications of this study.The results showed that the form of patrol carried out by the Sabhara Polres Bogor unit in order to prevent acts of theft by weighting at the Polres Bogor had been carried out through several systematic stages, namely Planning, Organizing, Actuating and Controlling. And the inhibiting factor is the lack of personnel, which is not proportional to the area covered to carry out patrols. Keywords : Patrol, theft with weight (Curat), Sabhara